The student newspaper survival guide - Kanigel, Rachele (Malden, MA : Wiley-Blackwell, 2012)
'The Student Newspaper Survival Guide has been extensively updated to cover recent developments in journalism and college newspapers as a result of technological advances; at the same time, it continues to successfully guide student journalists through the intricate process of producing a student newspaper. Extensively updated and expanded to discuss many of the changes in the field of journalism and in college newspapers, with two new chapters to enhance the focus on online journalism and technology Guides student journalists through the intricate, multi-step process of producing a student newspaper including the challenges of reporting, writing, editing, designing, and publishing campus newspapers and websites Contains updated examples of award winning student newspaper journalism in North America Chapters include discussion questions, exercises, and projects Now richly illustrated with over 100 images and examples in full color Essential reading for student reporters, editors, page designers, photographers, webmasters, and advertising sales representatives '--
'Student newspaper production has greatly evolved since the first publication of this book in 2006, with increased emphasis on their Web sites, and many taking a Web-first approach to publishing news and incorporating multimedia storytelling. New delivery devices and technologies for transmitting breaking news now exist, such as microblogging and streaming video from cell phones. Social networking tools have created the opportunity to communicate with readers and to disseminate news in different ways. This new edition of The Student Newspaper Survival Guide discusses how these rapid technological developments can positively affect the efficiency, effectiveness and creativity of student newspapers. At the same time, it continues to successfully guide student journalists through the intricate process of producing a student newspaper. Updated features of the second edition include: A new chapter on Social Media, including how to make use of Facebook, Twitter, CoveritLive and other tools to report and distribute news A new chapter on multimedia that explains the basic concepts of digital storytelling and offers tips on recording audio, shooting and editing video, producing slideshows and creating interactive graphics An expanded chapter on websites, including breaking news online Fresh, new, full colour examples from college newspapers around North America'--
Includes bibliographical references and index.
Keywords: College student newspapers and periodicals